Thematic Interpretation Study in Determining Indonesia’s Qibla through Takhsis - Sunarto, Sunarto; Muhammad Hariyadi (UIN Sunan Kalijaga Yogyakarta, 2022)
Ali Mustafa Yakub and the Majelis Ulama Indonesia (Indonesian Ulama Council) differed in their interpretation of the Indonesian qibla directon. According to the Indonesian Ulama Council, the qibla of Indonesia faces northwest, whereas Yakub believes it faces west. The Hisab Rukyat Board of the Indonesian Ministry of Religion, the Indonesian Ulama Council, Islamic organizations, and Islamic scholars (ulama) can use this research as a reference when determining the qibla. This study employs Abdul Wahhab Khallaf's takhsis theory in ‘Ilm Uṣūl al-Fiqh. In this investigation, both qualitative and quantitative methodologies were utilized. The Al-Qur'an is interpreted using the thematic interpretation procedure. This study concludes that the majority of the hadiths narrated by Tirmizī (the direction between east and west is the qibla) can be interpreted in light of verse 144 of surah al-Baqarah (turn your face toward the Masjid al-Haram). This takhsis theory classifies the direction of the Indonesian qibla into three categories: general (west), semi-specific (northwest), and special ('ainul Kaaba).